Long noncoding RNAs in C. elegans - Nam, Jin-Wu; Bartel, David P.

(untitled) (Genome Research, 2012)
Thousands of long noncoding RNAs (lncRNAs) have been found in vertebrate animals, a few of which have known biological roles. To better understand the genomics and features of lncRNAs in invertebrates, we used available RNA-seq, poly(A)-site, and ribosome-mapping data to identify lncRNAs of Caenorhabditis elegans. We found 170 long intervening ncRNAs (lincRNAs), which had single- or multiexonic structures that did not overlap protein-coding transcripts, and about sixty antisense lncRNAs (ancRNAs), which were complementary to protein-coding transcripts. Compared to protein-coding genes, the lncRNA genes tended to be expressed in a stage-dependent manner. Approximately 25% of the newly identified lincRNAs showed little signal for sequence conservation and mapped antisense to clusters of endogenous siRNAs, as would be expected if they serve as templates and targets for these siRNAs. The other 75% tended to be more conserved and included lincRNAs with intriguing expression and sequence features associating them with processes such as dauer formation, male identity, sperm formation, and interaction with sperm-specific mRNAs. Our study provides a glimpse into the lncRNA content of a nonvertebrate animal and a resource for future studies of lncRNA function.